Spinal SNAP-25 regulates membrane trafficking of GluA1-containing AMPA receptors in spinal injury–induced neuropathic pain in rats. (10th January 2020) - Liu, Peng; Song, Chengcheng; Wang, Chunyan; Li, Yize; Su, Lin; Li, Jing; Zhao, Qi; Wang, Zhen; Shen, Mengxi; Wang, Guolin; Yu, Yonghao; Zhang, Linlin
Highlights: Spinal injury promotes SNAP-25 expression and phosphorylation. Spinal membrane trafficking of AMPA receptor is increased in neuropathic pain. SNAP-25 inhibition reduces neuropathic pain and membrane trafficking of AMPA receptor. Inhibition of SNAP-25 phosphorylation alleviates neuropathic pain and AMPA receptor membrane trafficking. GluA1-containing AMPA receptor inhibition relieves neuropathic pain. Abstract: Introduction: Synaptosomal associated proteins of 25 kDa (SNAP-25), as a member of stable soluble N-ethylmaleimide-sensitive factor attachment protein receptor complex, is critical for membrane fusion and required for the release of neurotransmitters. The α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor is implicated in pathologic pain. This study aimed to investigate whether and how SNAP-25 regulated AMPA receptors in neuropathic pain. Methods: Male Sprague–Dawley rats underwent L4 spinal nerve ligation (SNL) or the sham procedure. After assessing mechanical allodynia and thermal sensitivity, the ipsilateral portion of the L4-5 spinal cord was harvested. The expression level of SNAP-25 was analyzed by Western blot analysis and real-time quantitative polymerase chain reaction. SNAP-25 phosphorylation and AMPA receptor membrane trafficking levels were evaluated with Western blot analysis. An association between SNAP-25 and AMPA membrane trafficking was confirmed by SNAP-25 expression or phosphorylation inhibition. Results: The SNL procedure induced and maintained mechanical allodynia and thermal hyperalgesia. SNL increased the expression and phosphorylation of SNAP-25 and the membrane trafficking of AMPA receptors in the spinal cord. SNAP-25 expression or phosphorylation inhibition alleviated neuropathic pain and downregulated membrane trafficking of AMPA receptors after SNL. GluA1-containing AMPA receptor inhibition relieved mechanical allodynia and thermal hyperalgesia after SNL. Conclusions: The upregulation of SNAP-25-dependent membrane trafficking of AMPA receptors via SNAP-25 phosphorylation at Ser187 contributed to SNL-induced neuropathic pain. Thus, the inhibition of SNAP-25 expression or phosphorylation might serve as a treatment for neuropathic pain. However, the mechanism of GluA1-containing AMPA receptor membrane trafficking mediated by SNAP-25 phosphorylation in neuropathic pain deserves further exploration.